Respuesta :

gmany

Answer:

y + 3 = -6(x + 9) - point-slope form

y = -6x - 57 - slope-intercept form

Step-by-step explanation:

The point-slope form of an equation of a line:

[tex]y-y_1=m(x-x_1)[/tex]

m - slope

The formula of a slope:

[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]

========================================

We have the slope m = -6 and the point (-9, -3).

Substitute:

[tex]y-(-3)=-6(x-(-9))\\\\y+3=-6(x+9)[/tex]

Convert to the slope-intercept form (y = mx + b):

[tex]y+3=-6(x+9)[/tex]           use the distributive property

[tex]y+3=-6x-54[/tex]         subtract 3 from both sides

[tex]y=-6x-57[/tex]